Performance analysis of SEP, I-SEP, PSO and WCA-based clustering protocols in WSN. (16th January 2020) - Gambhir, Ankit; Payal, Ashish; Arya, Rajeev
Wireless sensor networks (WSNs) are significantly resource restrained by their delimited power supply. Hierarchical routing based on clustering is an effectual methodology; however, preferring an energy-sensible cluster by optimally selection of cluster head (CH) is also very perplexing. In the present paper, performance analysis of the hierarchical routing protocols based on clustering such as stable election protocol (SEP), improved stable election protocol (I-SEP), conventional low-energy adaptive clustering hierarchy (LEACH) and optimised versions of LEACH based on nature motivated optimisation algorithm such as particle swarm optimisation (PSO) (derived from swarm intelligence) and water cycle algorithm (WCA) (derived from observing how rivers and streams flow to the sea) are presented. Numerous parameters have been well-thought-out as the base of the study to present useful results in comparison of clustering protocols in WSN that lead to noteworthy findings in the form of results. The study is examined over a variety of performance metrics such as alive nodes per round, packet to base station (BS) per round and dead nodes per round. Based on the thorough consideration and observations, a qualitative conclusion is also drawn at the end.